Transformational leadership and employee voice for product and process innovation in SMEs (INMR - Innovation & Management Review, 2021)
Purpose – This study aims to investigate the impact of transformational leadership on the innovation ofsmall and medium enterprises (SMEs) through employee voice behaviors. Drawing from the upper echelontheory, it is hypothesized that employee voice is the mediating mechanism through which transformationalleadership affects the process and product innovation in SMEs.Design/methodology/approach – Data was collected from 169 SMEs of Pakistan through an onlineself-administered questionnaire. The proposed hypotheses were tested using partial least squares structuralequation modeling (PLS-SEM).Findings – Findings confirm that transformational leadership positively affects both process and productinnovation in SMEs and employee voice behavior mediates between these relationships.Originality/value – This research contributes to both theoretical and practical domains by providingevidence that encouraging employees to raise their voice positively impacts product and process innovationand transformational leadership is a potential organizational factor to shape employee voice and process andproduct innovation. To the best knowledge, this is the first study that investigates the mediating role ofemployee voice between transformational leadership and process and product innovation in SMEs anddeveloping country’s context.